Highly efficient Rhizobium rhizogenes-mediated hairy root transformation for gene functional study in mung bean (Vigna radiata (L.) R. Wilczek) - Xuan Cuong, Nguyen; Thi Loan, Tran; Khanh Linh, Chu; Thi Dong, Ta; Phuong Thao, Bui; Tien Phat, Do (Vietnam Journal of Biotechnology, 2023)
Mung bean (Vigna radiata (L.) R. Wilczek) is one of the economically important legume crops in Asia. The demand for high quality mung bean seeds is currently increasing. Moreover, the crop can fix the atmospheric nitrogen. Those make the crop is suitable for sustainable agriculture and a major source of the plant-based protein foods. Functional genomics study in mung bean is required to comprehend the molecular mechanisms behind agronomic traits and elevate the crop trait improvement process; however, it is severely hampered due to the lacking of efficient and large-scale genetic analysis tool. Rhizobium rhizogenes-mediated hairy root transformation is a quick and efficient alternative to investigate root-specific processes and interactions in different species. In this study, we developed a protocol to generate hairy roots with low cost and high transformation efficiency that has not been reported in mung bean. Using the method, nearly 100% of the R. rhizogenes infected plants formed hairy roots and carried at least three transgenic roots harboring the desired construct per plant. It only required twenty days to complete the whole transformation process. In addition, the composite plants, that are composed transgenic roots and wild-type shoot, were used to examine with the fixing nitrogen bacteria and showed the GUS expression in nodules. In conclusion, our highly efficient R. rhizogenes-mediated transformation system provides high throughput genetic analysis assay for functional genetics study, and biotechnological application in mung bean.